Kids make music! clapping & tapping from Bach to rock - Hart, Avery; Braren, Loretta Trezzo; Mantell, Paul. (Charlotte, Vt. Williamson Pub., 1993)
Presents a variety of activities based on music, including singing and dancing, improvisation, and making homemade instruments.
Keywords: Games with music; Games with music; Music; Musico-callisthenics.